Proposta de gerenciamento de dados para monitoramento de saúde estrutural utilizando redes de sensores ópticos FBG - SANTOS, Adam Dreyton Ferreira dos (Universidade Federal do Pará, 2014)
Due to their unique characteristics, optical sensor networks have found application in many fields, such as in Civil and Geotechnical Engineering, Aeronautics, Energy and Oil & Gas Industries. Monitoring solutions based on this technology have proven particularly cost effective and can be applied to large scale structures where hundreds of sensors must be deployed for long term measurement of different mechanical and physical parameters. Sensors based on Fiber Bragg gratings (FBGs) are the most common solution used in Structural Health Monitoring (SHM) and the measurements are performed by special instruments known as optical interrogators. Acquisition rates increasingly higher have been possible using the latest optical interrogators, which gives rise to a large volume of data whose manipulation, storage, management and visualization can demand special software applications. This work presents two real-time software applications developed for these purposes: Interrogator Abstraction (InterAB) and Web-based System (WbS). The innovations in this work include the integration, synchronization, independence, security, processing and real-time visualization, and data persistence or storage provided by joint work of developed applications. The results obtained during tests in laboratory and real environment demonstrate the efficiency, robustness and flexibility of these softwares for different types of sensors and optical interrogators, ensuring atomicity, consistency, isolation and durability of data persisted by InterAB and displayed by WbS.